2013
DOI: 10.1103/physrevlett.110.257001
|View full text |Cite
|
Sign up to set email alerts
|

Avoided Quantum Criticality and Magnetoelastic Coupling inBaFe2xNixAs2

Abstract: We study the structural and magnetic orders in electron-doped BaFe2−xNixAs2 by high-resolution synchrotron X-ray and neutron scatterings. Upon Ni-doping x, the nearly simultaneous tetragonalto-orthorhombic structural (Ts) and antiferromagnetic (TN ) phase transitions in BaFe2As2 are gradually suppressed and separated, resulting in Ts > TN with increasing x as was previously observed. However, the temperature separation between Ts and TN decreases with increasing x for x ≥ 0.065, tending towards a quantum bi-cr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
103
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 86 publications
(112 citation statements)
references
References 33 publications
(52 reference statements)
7
103
0
2
Order By: Relevance
“…Since an obvious difference between FeSe 1−x S x and Ba-122 systems is the lack of AF order in the former, the large thermal critical fluctuations present in the underdoped Ba-122 samples may be attributed to the fluctuations of striped AF order [28][29][30][31], which gives the same rotational symmetry breaking as the nematic order. This is consistent with the suggestion that no AF QCP presents in these materials [12][13][14] and thus the AF order only contributes to thermal fluctuations along the (110) direction.…”
supporting
confidence: 79%
See 2 more Smart Citations
“…Since an obvious difference between FeSe 1−x S x and Ba-122 systems is the lack of AF order in the former, the large thermal critical fluctuations present in the underdoped Ba-122 samples may be attributed to the fluctuations of striped AF order [28][29][30][31], which gives the same rotational symmetry breaking as the nematic order. This is consistent with the suggestion that no AF QCP presents in these materials [12][13][14] and thus the AF order only contributes to thermal fluctuations along the (110) direction.…”
supporting
confidence: 79%
“…Both the AF order and the structural transition disappear around the optimal doping level, indicating the presence of magnetic and/or nematic quantum critical points (QCPs). While there is increasing evidence that the magnetic QCP may not exist in many materials [12][13][14][15][16], the nematic QCP has attracted more and more interest since nematic quantum fluctuations may induce an attractive pairing interaction and thus enhance or even lead to superconductivity [17][18][19].So far, the evidence for the nematic QCP is rather limited. It is shown that the nematic order may go through a zero-temperature order-to-disorder quantum phase transition as shown by elastoresistance [3,9], elastic constants [4,5], and Raman scattering [7,8].…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…The green shaded region denotes the presence of a tetragonal AF phase. (d) Similar phase diagram for electron-doped BaFe2−xNixAs2 (Lu et al, 2013;Luo et al, 2012b). Here the incommensurate (IC) AF order is a spinglass phase coexisting and competing with the superconducting phase (Lu et al, 2014b).…”
Section: Static Antiferromagnetic Order and Its Doping Evolutionmentioning
confidence: 99%
“…Figure 5(d) shows the phase diagram of electron-doped BaFe 2−x Ni x As 2 obtained from X-ray and neutron scattering experiments (Lu et al, 2013;Luo et al, 2012b). Here, the AF order decreases with increasing Ni-doping and disappears near optimal superconductivity in a first order like fashion with an avoided quantum critical point (Lu et al, 2013).…”
Section: Static Antiferromagnetic Order and Its Doping Evolutionmentioning
confidence: 99%